The Impact of Erasmus+ Programs on the Careers of Generations Y and Z - Alexandra-Ioana POPESCU; Denisa ABRUDAN (Revista de Management Comparat International)
This paper aims to highlight the impact of Erasmus+ mobility programs on future career prospects among young people aged 13 to 30 from European Union countries. For the research, a questionnaire was created and assigned to young people from generations Y and Z, who participated in at least one Erasmus+ mobility, within the Cloud Five Association, in various short-term youth exchanges. Based on the answers received in the questionnaire, we find out the opinion of 85 young people about the influence that such projects have had on improving the quality of their lives. Finally, we outline an overview of the real impact of these programs on the careers of young people. The results of the research show the high impact of short-term mobilities, such as youth exchanges, on their career prospects.